PENERAPAN HUKUM STATUS AHLI WARIS BEDA AGAMA DALAM SOSIOKULTURAL MASYARAKAT JAWA - Anwar, Khoerul; Maula, Bani Syarif (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2022)
Inheritance is the transfer of property from the heir to the heir after the heir dies and the transfer process is valid according to applicable law. This type of library research (library research) in which researchers collect data from the literature. The research object that the author focuses on is how the application of the distribution of inheritance law in the land of Java, in relation to positive law and Islamic law in Indonesia. In reality, the division of inheritance in the land of Java prioritizes deliberation rather than directly applying the applicable law. The approach method used by the author is a qualitative method to view data from a quality perspective. The source of this research is divided into 2, namely primary and secondary. The primary sources in this study are law number 1 of 1974 concerning marriage and the Civil Code as material for analysis, while secondary sources are writings such as journals, books or others related to the research theme.